2018
DOI: 10.1080/01490400.2018.1426064
|View full text |Cite
|
Sign up to set email alerts
|

Injustice in Mobile Leisure: A Conceptual Exploration of Pokémon Go

Abstract: In augmented reality, video games and the physical world converge as individuals participate in digital leisure overlaid on physical spaces. In Pokémon Go, game play in the physical world is impacted by constraints that limit access and play of marginalized groups. Global popularity of Pokémon Go created an opportunity to explore experiences of marginalized groups participating in augmented reality game play. Grey literature surrounding Pokémon Go is rich with accounts of constraints experienced by marginalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Previous studies on female players primarily focused on discrimination in the game, with the idea that leisure scholars should be aware of social justice (Schultz and McKeown, 2018). Layland et al (2018) asserted that marginalized groups faced the same limits in gaming as they experienced in real life. Xue et al (2019) found that female participants in esports still faced gender discrimination.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Previous studies on female players primarily focused on discrimination in the game, with the idea that leisure scholars should be aware of social justice (Schultz and McKeown, 2018). Layland et al (2018) asserted that marginalized groups faced the same limits in gaming as they experienced in real life. Xue et al (2019) found that female participants in esports still faced gender discrimination.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Hegemonic masculinity, as a set of rules and social expectations, dictates important sex, power, and relationship roles for men (Duncanson, 2015;Szabo, 2014). Changing social norms notwithstanding, traditional masculine roles of provider, leader, and 'king of the castle' remain influential in the dating lives of men (Kimmel, 2017), and young men continue to enact the troubling gendered promiscuity dualism of male 'studs' and female 'sluts' (Flood, 2013;Lai & Hynie, 2011). As a result, men are confronted with both calls to enact masculinities in new ways reflexive of changing social norms, and deep western traditionalism of misogynistic and patriarchal actions.…”
Section: Masculinities and Gendermentioning
confidence: 99%
“…Hjorth and Richardson’s (2017) collection of short commentaries balances the pro-social and generative affordances of AR gameplay with a number of critical interventions, including how players use mobile interfaces to avoid social interaction (Humphreys, 2017); the corporate appropriation of public space (Sicart, 2017), surveillance and asymmetric visibility between players and Niantic (de Souza e Silva, 2017), and locative inequalities in physical space (Salen Tekinbaş, 2017). Other critical work shows how marginalized populations do not experience the same freedom of mobility and positive interactions as non-marginalized players (Layland et al, 2018). For the most part, however, journalistic and scholarly writing on Pokémon Go is overwhelmingly positive, celebrating how the game produces healthy bodies and social ties.…”
Section: Introductionmentioning
confidence: 99%